Pengaruh Komunikasi Persuasif dan Hasil Belajar Mata Kuliah Kewirausahaan terhadap Keputusan Pembelian - Puspitaningsih, Flora; Ningsih, Erni Wulan; Santosa, Agus Budi; Febrianto, Rohmat (LPPM Universitas PGRI Argopuro Jember, 2024)
This research aims to obtain information regarding the influence of persuasive communication and the final results of studying entrepreneurship courses on purchasing decisions made simultaneously and partially. This research method is non-experimental quantitative. The population used was STKIP PGRI Trenggalek students. The sample was determined using a probability sampling technique with simple random sampling with a total of 88 students. Data collection for this research used a questionnaire. The data analysis used is simple linear regression, multiple linear regression, t test and F test. The results of this study show that there is a positive influence of persuasive communication (X1) on purchasing decisions (Y) as evidenced by tcount (6.397) > ttable (1.987) with significance 0.000 < 0.050, which means there is an influence between persuasive communication on purchasing decisions. There is a negative influence on the results of studying entrepreneurship courses (X2) on purchasing decisions (Y) as evidenced by the value of tcount (-1.316) < ttable (1.991) with a significance of 0.192 > 0.050, which means there is no influence between learning outcomes of entrepreneurship courses on purchasing decisions. The results of the F test (simultaneous) in this study show the value of Fcount (21.541) > Ftable (3.10) and a significance level of 0.000